(untitled) (Fiep Bulletin - online, 2014)
The wind is one of the greatest allied since the foundations of the humanity. The use of the boat the candle more than retraces a history of five a thousand years, and its evolution led to originate the sport the candle and its boats. The majority of the new sailors is initiated in this sport through a candle school that instructs pupils of diverse ages, between these new sportsmen they are children who, had its early cognitive development, process difficulty for the recognition of the element of the nature, wind being important, then that the methodologies of these institutions if withhold of significant form in the education of the wind and its functioning, since this is the main point for the learning of this sport. Practical of the instruction of the this sportive modality and pedagogical knowledge of the Physical Education they are important to adapt an education process/learning that allows to the assimilation of the diverse important factors for the education of the sport the candle. This inquiry promoted a series of evaluations on the application of the methodology of education created for the Yacht School of Candle in the year of 2007 and its capacity technique to carry through the assimilation of this knowledge in its pupils who are understood in the age of seven band the eleven years; another observed point was the educational process, its pedagogical progression and practical exercises comparing with the project “There Main with there the Pate” of the Academy of Sciences in France and its national version “the Hand in the Mass”; it was still verified, if this methodology is in accordance with diverse authors and educational agencies. It was objectified in such a way, to give solution to the central problem that is: the methodology of education of the recognition of the wind and its direction, effected by the Yacht School of Candle, in seven children the eleven years, have theoretical base and technique that its efficient application allows?